2007
DOI: 10.1080/00222930701689937
|View full text |Cite
|
Sign up to set email alerts
|

Revision of thehirsuticornis‐like species ofMacrothrixBaird, 1843 (Cladocera: Anomopoda: Macrothricidae) from Subantarctic and temperate regions of the southern hemisphere

Abstract: The aim of this paper is to revise populations of Macrothrix cf. hirsuticornis (Cladocera: Anomopoda: Macrothricidae) from different regions of the southern hemisphere. It is demonstrated that M. hirsuticornis Norman and Brady, 1867 s. str. is absent there, and five related species occupy different Subantarctic islands and the southernmost portions of South America, and Africa. Macrothrix boergeni Studer, 1878 from the Kerguelen Archipelago is redescribed and a neotype is selected. All populations in the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…However, lower endemism in South Africa (Korovchinsky, 2006) can be attributed to an insufficient level of study, confirmed by recent findings (Kotov 2007b(Kotov , 2009Sinev, 2008Sinev, , 2009; this study). Segers and De Smet (2008) also concluded that there are few known rotifer endemics in the Cape region, but that this is probably due to the absence of data, rather than being a fact (H. Segers, personal communication).…”
Section: Taxonomical Effortssupporting
confidence: 70%
See 2 more Smart Citations
“…However, lower endemism in South Africa (Korovchinsky, 2006) can be attributed to an insufficient level of study, confirmed by recent findings (Kotov 2007b(Kotov , 2009Sinev, 2008Sinev, , 2009; this study). Segers and De Smet (2008) also concluded that there are few known rotifer endemics in the Cape region, but that this is probably due to the absence of data, rather than being a fact (H. Segers, personal communication).…”
Section: Taxonomical Effortssupporting
confidence: 70%
“…There are doubts on their origins: they could not be regarded as primitive, but assuming that the crowngroup is very old (=possibly even as far as the Mesozoic), they could be regarded as descendants of a proto-taxon with a pan-continental distributional area. The same is true for Macrothrix sarsi, an endemic member of the hirsuticornis-group (Kotov, 2007b). The endemic genus Dumontiellus Smirnov, 2007 is another example of a South African rock-pool endemic from high altitudes, and so is Pleuroxus carolinae (Smirnov, 2007;Smirnov et al, 2006).…”
Section: South Africa As a Centre Of Cladoceran Endemism: The Importamentioning
confidence: 77%
See 1 more Smart Citation
“…12I). At the same time, in other Macrothrix species with known morphology (KOTOV, 1999b(KOTOV, , 2007b Fig. 11G) no such transformation of the form of the posterior setae of thoracic limbs takes place.…”
Section: Wwwrevhydrocommentioning
confidence: 94%
“…A tendency for reduction of the number of posterior setae is strong in the chydorid line. In Bosmina, Ophryoxus and Macrothrix, the series of posterior setae is incomplete; only remnants of this series are present (e.g., see KOTOV, 1999bKOTOV, , 2007b, see also Fig. 10A, C).…”
Section: Wwwrevhydrocommentioning
confidence: 97%